Ideology at Work: Language as Performative Discourse - Abdelghani , Nait-Brahim (Richtmann Publishing, 2012)
Language policy and practice in Algeria is subject to an extreme ideological dispute that has accompanied political, culturaland social life since independence. In a rich linguistic arena, where four languages (standard Arabic, Algerian spoken language, Berberand French) interact as much as they compete, political and religious ideologies, by instrumentalizing standard Arabic, have had theirshare in directing policies and developing representations that serve political interests, often at the expense of a peaceful and fruitfulcoexistence within a diverse linguistic market. The question raised here is the following: how does standard Arabic serve politicalinterests, despite the fact that its political status totally contradicts its real sociolinguistic one? With a colinguism being set as a rule forlanguage policy, standard Arabic, religion and politics have come to form a triad whose purpose is to maintain conditions for aperformative ideological discourse whose permanence needs the people’s consent and rallying belief in a community of believers. Themain goal of such a state is to exclude the vast majority of the population from the field of political debate and reflexion, and discardoppositional intellectuals who do not use standard Arabic.